Prevalence of lower urinary tract symptoms in patients undergoing inguinal hernia repair - Jain, Sudhir Kumar; Hameed, Tariq; Sundarraj, Shankar; Manzar Ansari, Faiz (International Surgery Journal, 2019)
Background: Lower urinary tract symptoms (LUTS) are frequently associated with inguinal hernias. It is important to recognise and treat bladder outlet obstruction in patients before inguinal hernia repair to prevent recurrence of hernia. Methods: This prospective study was conducted at Maulana Azad Medical College. Hundred patients who presented with inguinal hernia repair were evaluated for LUTS using AUA scoring for urinary symptoms, uroflowmetry (Qmax) and post voidal residual urine using ultrasonography along with urine routine microscopic examination and urine culture and sensitivity. Results: Eleven patients out of 100 who came for hernia repair had clinically significant LUTS due to benign enlargement of prostate (BEP) and required treatment for BEP but none of these 11 patients had urinary symptoms as primary complaint. Ten patients were found to have urinary tract infection without any urinary symptom. Three patients had urethral stricture out of which 2 had Qmax of <10 ml/second. Conclusions: Significant number of patients (14 percent) with inguinal hernia had lower urinary tract symptoms. An effort should be made to identify LUTS in patients presenting with inguinal hernia before surgery and treat the cause of LUTS. Ten percent of patients had asymptomatic UTI with AUA score less than 8 but Qmax on uroflowmetry was in between 10-15 ml/second.